‘PRi special edition: The intersections between public relations and neoliberalism’ – The road to nowhere: Re-examining activists’ role in civil societies - Wolf, Katharina (SAGE, 2019)
The French sociologist Pierre Bourdieu (1977) argued that the presence of critical counter-voices and powers is a fundamental element of any genuine democracy. However, in Australia these counter-voices are increasingly marginalized and threatened by controversial laws that would limit the legal standing of conservation groups and the use of overseas donations for advocacy purposes based on the argument that “systematic, well-funded” environmental campaigns are threatening the nation’s economic prosperity. Drawing on social movement theory and Bourdieu’s theory of practice, this case study details the final months of the Save Beeliar Wetlands campaign in the lead up to the 2017 West Australian state election. The author challenges three common assumptions in the extant PR activism literature: The existence of activists in opposition to organizations and governments, the presence of a ‘zone of compromise’ between activists and the organizations or governments whose actions they are opposing and the conceptualization of activists as homogenous entity. Evolving into a colorful collective of over 35 local groups, five local councils and thousands of individuals, Beeliar Wetland Defenders successfully created an alternative narrative to the State and Federal Governments’ neoliberal agenda. Activists thereby contributed significantly to a change in leadership and the termination of a $1.9billion infrastructure project. This paper argues that activist groups’ interventions in public debate perform a valuable societal voice as critical counter-voices in challenging established hierarchies and power relationships. However, in mounting and framing their arguments within the neoliberal framework, activist groups may also inadvertently reinforce this worldview.